O coronelismo ainda respira: atributos do universo coronelista na conjuntura político-eleitoral de municípios do Maranhão para os cargos de deputado estadual e federal nas Eleições 2018. - GUIMARÃES, Pedro Henrique (2023)
The present dissertation conveys an endeavor in demonstrating the presence of idiosyncrasies of the coronelist ideology in municipalities from Maranhão using as reference the 2018 general elections to state deputy and federal deputy offices, that is to say, if some customs and characteristics of the coronelist system – as it was conceived by Victor Nunes Leal – were preserved in current times, which statutes and improvements originated from said system and how can we infer if said attributes could be identified in the electoral backdrop in allusion. The undertaken endeavor comes about with the aim of verifying if the institute of coronelism – considering its many facets – was extinct or not from the Brazilian sociopolitical conjuncture, electing the State of Maranhão, by means of specific municipalities selected with observance of objective criterion – namely the prevalence of rural properties or urban properties in the complexion of these municipalities –, as space for said scrutiny to be operated. Likewise, it had been chosen as an object of study, the 2018 general elections to state deputy and federal deputy offices, recognizing said circumstance as the most adequate to, eventually, the features of coronelist character to manifest in the results of said contest more evidently – given the method of analysis of the operated content –, considering the greater proximity the applicants to said offices may preserve with local leadership. For better comprehension of the chosen theme and its influences on said relations, we analyzed – through pronounced bibliographic review – the development of coronelism and its predicates throughout Brazilian history, as well as revisited concepts that preserve strict connection with the coronelist ideology – with concern to the established social relations –, e.g: political pratonage, bossism, eletronic coronelism and neocoronelism. Still, we sought to scrutinize the path which traditional and classic coronelism engaged, given that the essence of this system created new unfoldings of said concept for the viability of “power adjustments” to adapt ulterior social, economic and political realities, an used resource by determined political strata for the maintenance of favoritism in the means that it exercises its influences